Programa semipresencial de habilidades sociais para professores: características dos cursistas e indicadores de processo e resultado - Cintra, Amelie Bussolan (2018)
It´s noticed the need and importance of preparing teachers to deal with the challenges that interfere in the teaching and learning process, as well as with the interpersonal demands of their personal and professional life. The theoretical-practical field of Social Skills presents resources for that, with evidences of effectiveness and efficiency of face-to-face teacher´s programs. In order to this training reach the teaching community, it is crucial to investigate modalities of disseminating these practices with evidence of effectiveness. This research evaluated the first module of a social skills course for teachers by investigating the relationships between the characteristics of the teachers-trainees (sociodemographic data, professional performance, technology domain, professional self-evaluation, understanding about social-emotional development and classroom management), the program process (attendance, quality of engagement, course aspects) and results (social skills performance and knowledge). The program was conducted in the blended learning mode, with six units, totaling 40 hours of face-to-face activities and in the virtual learning environment. Participated eleven teachers of the 1st to 5th year of elementary public school, who answered the IHS-Del-Prette (version 2016) and a knowledge questionnaire about social skills, as well as personal information and conceptions. Moreover, the performance of the teachers throughout the program were also evaluated by tutors. The data were analyzed descriptively and inferentially (Student's t, Wilcoxon and Spearman's Correlation). The results have indicated that the program was effective in indicators of social skills reporting, measured by IHS-Del-Prette, in the total score (t(10)=2,43; p=0,035; g=0,24), skills of social self-exposure in F4 (t(10)=2,46; p=0,034; g=0,71) and in affective-sexual assertiveness skills in F5 (t(10)=2,25; p=0,049; g=0,42), as well as by improving acquisition of knowledge, evaluated in the open questions (Z=-2,76; p=0,003; r=-0,59), closed (t(10)=3,022; p=0,013; g=0,80) and total score (Z=-2,93; p=0,001; r=-0,63). It was found significant and negative correlations between sociodemographic variables (age, time from graduation and professional experience) and the variables of process (notes for improvement of tasks, managing the virtual environment and overall course performance) and outcome (social skills performance), as well as positive correlations between the students' initial self-assessment (in social skills assertive, emotional self-control, conflict management) and the teacher´s improvement of their social self-exposition assertiveness ability. The data reinforce the importance to considering the initial characteristics of teachers as a way to plan aspects of the process and in the establishment of conditions for in service teacher´s programs. Limitations and implications of the results of this pilot study are discussed along the thesis.